POLITICAL ECOLOGY AND GOOD GOVERNANCE: DISCOURSE ON MULTI-STAKEHOLDER ENGAGEMENT IN ACHIEVING SUSTAINABLE DEVELOPMENT THROUGH PT CIKARANG LISTRINDO TBK PLGTU JABABEKAS CORPORATE SOCIAL RESPONSIBILITY PROGRAM - Rahman, M. Ridha Taufiq; Simarmata, Kisvan; Pradipta, Ganuardi; Farida, Lita Rizqi; Nurhasanah, Yanti (Department of Government, FISIP, Universitas Padjadjaran, 2022)
This study seeks to examine the practice of Corporate Social Responsibility (CSR) carried out by PT Cikarang Listrindo Tbk PLTGU Jababeka from the point of view of Political Ecology and good governance, especially in the scope of discourse that sees this CSR program as a form of multi-stakeholder involvement as an effort to address social, economic, and environmental problems to create sustainable development. This study uses a qualitative approach with exploratory research methods. This research was conducted in Karangharja Village, North Cikarang District, Bekasi Regency. Primary data sources were obtained from in-depth interviews, while secondary data were obtained from documents and literature related to the research topic. The results of the study indicate that the power relations between stakeholders that are formed from the construction of discourse associated with the implementation of CSR by the business sector as an effort to achieve sustainable development can move these stakeholders to get involved and participate in the implementation of the CSR Program initiated by PT Cikarang Listrindo Tbk PLTGU Jababeka. Through the power relations formed from ideas related to the implementation of this CSR program, the desire and willingness of other stakeholders to participate in the CSR program initiated by PT Cikarang Listrindo Tbk PLTGU Jababeka can make the execution of the CSR program have an impact on the social and economic life of the community, along with environmental sustainability efforts.gb777